# Find the value of polynomial using given values for x.i. x = 3 ii. x = -1iii. x=0

The given polynomial is as follows:

2x – 2x3 + 7

(i) Put x = 3 in the given polynomial

= 2 × 3 – 2 × (3)3 + 7

= 6 – 2 × 27 + 7

= 6 -54 + 7

= -41

(ii) Put x = -1 in the given polynomial

= 2 × (-1) – 2 × (-1)3 + 7

= -2 + 2 + 7

= 7

(iii) Put x = 0 in the given polynomial

= 2 × 0 – 2 × (0)3 + 7

= 0 + 0 + 7

= 7

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Champ Quiz | Polynomials29 mins  Methods to find zeroes of a Polynomial-246 mins  Remainder Theorem and Factor Theorem38 mins  Polynomials - Zero to Hero42 mins  Genius Quiz | Polynomials40 mins  Zeros and Degrees of a Polynomial41 mins  Introduction to Polynomials37 mins  Basic understanding of Polynomials37 mins  Quiz | Imp. Qs. on Algebraic Identities65 mins  Genius Quiz | Division of Algebraic Expressions37 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 